Evaluation of Intra and Inter-specific Variability among Species of Curcuma using Microsatellite Markers - Thomas, Bimal; Asha, KI; Krishna Radhika, N (JOURNAL OF ROOT CROPS, 2018)
Microsatellite markers such as ISSRs and SSRs were used to study the genetic variability among 15 selected accessions in 8 species of Curcuma germplasm comprising of two accessions in each of the seven Curcuma species and one of C. longa. Of the primers tested, 10 (out of 10) ISSR and 7 (out of 10) SSR primers were selected for their reproducibility and high polymorphism. A total of 166 polymorphic ISSR bands were detected out of 176 bands and a total of 123 polymorphic SSR bands were detected out of 135 bands. Results demonstrated an extensive genetic variability within the selected accessions as well as the value of ISSR and SSR markers in characterization of Curcuma species. Marker scoring data was used to construct UPGMA dendrogram and Pearson Correlation Coefficient. For both markers a high similarity in dendrogram clustering was obtained. All dendrograms, including that obtained by the combined use of both the ISSR and SSR marker data, depicted the genetic relationship/variability among the accessions, depending upon their species similarity/dissimilarity.